Infotainment: Kebebasan atau Kebablasan Ditinjau dari Kajian Ekonomi Politik Media - Setiowati, Endang (Bina Nusantara University, 2010)
Infotainment as delivered on television occurs to be one controversial TV shows, often accused as a program that practically a